Decolorization of Methylene Blue from Aqueous Solution Using Mg-Fe-Al Layered Double Hydroxides with H2O2 - Tien Thao, Nguyen; Thi Trang, Do (Asian Journal of Chemistry, 2013)
A series of Mg-Fe-Al layered double hydroxides (LDHs) with different ratios of Mg/((Fe + Al) has been prepared and characterized by XRD, FT-IR. BET, SEM and TEM. The experimental data indicated that all the samples present a well-structured hydrotalcite, uniform particles or palettes and layered structures. The synthesized materials have used as catalysts/adsorbents for the decolorization of methylene blue in water. The preliminary results showed that Fe-containing hydrotalcites play as an active catalyst for the oxidation of methylene blue while the Fe-free sample acts as an adsorbent. The methylene blue conversion obtained over Mg-Fe-Al hydrotalcites was ca. 50-55 % at an ambient condition, but significantly improved as treated at a higher temperature or under UV light. The conversion of methylene blue approaches ca. 75-90 % under UV-light or higher temperature.